How do you simplify 5( d + 3) + 3( d - 2)?

2 Answers
Mar 18, 2018

See the following :)

Explanation:

First, you need to expand the brackets.

5(d+3)+3(d-2)
=d*5+3*5+d*3-2*3
=5d+15+3d-6

Then, you can group the like terms together as the following:

=(5d+3d)+(15-6)
=8d+9

Here is the answer for the question. Hope this can help you :)

Mar 18, 2018

8d+9

Explanation:

5(d+3)+3(d-2)

first, distribute the 5. that means multiply the five by everything inside the parentheses.

5d+15+3(d-2)

then, distribute the 3

5d+15+3d-6

finally, combine like terms

8d+9